Communication Pattern Strategies Dependent on the Transgression of Professional Sports Teams - Sang Hyun Lee; Philsoo Kim (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study was to synthetically explore different communication strategy patterns that are dependent on the events and stakeholders, which include professional sports players, teams, and the associations. METHODS Using the Python program, we performed web crawling and machine learning algorithms to analyze news articles for our research analyses. In particular, 696 articles on driving under the influence (DUI) of alcohol were gathered and subject to descriptive scrutiny; a total of 782 sentences were selected for the analysis. Also, among the 509 articles on illegal gambling, 484 sentences were analyzed. Moreover, 50 frequently reported words were extracted from these sentences to assess their frequencies through the word cloud method for concrete visualization. Then, the data were mapped in order to systemically understand the communication strategy patterns for each case, which were dependent on the stakeholders and timing of the event. RESULTS The empirical results revealed that in case of unethical events of driving under the influence that were reported in the news, most of the subjects chose an apology strategy immediately, but for illegal gambling reports, the parties involved rarely respond and it was difficult to find specific strategy patterns among the subjects. CONCLUSIONS The present study reveals that when professional sports teams were exposed to transgression, depending on the characteristics of the event and stakeholders, they chose different communication strategies involving fan characteristics for the event and subjects. Ultimately, they chose different strategies dependent on their fans' involvement.